STUDI KANDUNGAN DAN BEBAN PENCEMARAN LOGAM TIMBAL (Pb) PADA AIR BALAS KAPAL BARANG DAN PENUMPANG DI PELABUHAN TANJUNG EMAS SEMARANG - Azmi Umi Anisyah; Tri Joko; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The increasing of port activities causes increased pollution in the waters of the port due to ship waste. The ballast water is one of ship less waste monitored in the exchange activity. The purpose of this research is to determine content and the burden of the heavy metal pollution Lead (Pb) in the ballast water cargo and passenger ships. The type of research that used is descriptive survey with cross sectional approach. The variables of this research is content and pollution load by Lead (Pb) from ship ballast water. The research subjects are cargo and passenger ships that rely on the port of Tanjung Emas Semarang and carry ballast water which is limited by the inclusion and exclusion criteria as many as 30 ships. Measuring the levels of Lead using Atomic Absorption Spectrophotometry (AAS) methode get a result that there are 1,12 to 4,12 mg/l with an average value of 2,59 mg/l of lead metal in ship ballast water. Calculation of lead pollution load due to the disposal of ship ballast water get an average value up to 0,83 kg/day with range value 0,01-5,46 kg/day. There are 8 ships consist of 1 passenger ship and 7 cargo ships that have a value of more than average pollution loads.The conclusion of this study is the lead content in all samples of cargo and passenger ships ballast water have a value above the quality standart by Permen LH No 5 of 2014 on Industrial Waste Quality Standart that is equal to 0,01 mg/l. Ship ballast water discharge to some extent has contributed to lead pollution in the waters of Tanjung Emas in Semarang.